Activities of the International Research Centre for Late Antiquity and Middle Ages in 2005 and 2006 - Jurković, Miljenko (Array, 2007)
An Editorial describing the activities of IRC for Late Antiquity and Middle Ages (Zagreb-Motovun) in 2005 and 2006. During these years, the IRC for Late Antiquity and Middle Ages continued with field research. Till 2007 some of the archaeological excavations in Guran were concluded (three-aisled basilica, St. Simeon), others started (St. Cecilia, old settlement of Guran). The research activities of the Centre were expanded in 2005 by the archaeological excavations at the island of Rab (Kaštelina), as well as in Osor (monastery complex). The Centre is a coordinator of the European project "Corpus of European architecture of the first millennium". In late 2006/early 2007 the project IRCLAMA was approved, financed by the funds of European Commission .